2002
DOI: 10.4049/jimmunol.168.2.825
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Mitogen-Activated Protein Kinase Signaling Pathway Is Instrumental in Determining the Ability ofMycobacterium aviumto Grow in Murine Macrophages

Abstract: Of the two common morphotypes of Mycobacterium avium, designated smooth transparent (SmT) or smooth opaque (SmO), the SmO morphotype is avirulent, whereas the SmT morphotype is virulent. The role of the host macrophage in determining these different virulence phenotypes was analyzed using an in vitro model of macrophage infection. Initial studies confirmed previous reports of the increased ability of the SmT bacteria to grow in macrophages; this increased virulence correlated with reduced induction of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 48 publications
5
90
1
Order By: Relevance
“…PI3K is a conserved family of signaling molecules that are involved in regulating cellular proliferation and survival. Recent data suggest that the PI3K-Akt pathway is activated in macrophages upon mycobacterial infection or treatment with mycobacterial glycolipids (55)(56)(57). We show that PI3K activity, as defined by Akt phosphorylation, was activated at higher levels upon infection with M. smegmatis compared with M. avium-infected macrophages.…”
Section: Discussionmentioning
confidence: 54%
“…PI3K is a conserved family of signaling molecules that are involved in regulating cellular proliferation and survival. Recent data suggest that the PI3K-Akt pathway is activated in macrophages upon mycobacterial infection or treatment with mycobacterial glycolipids (55)(56)(57). We show that PI3K activity, as defined by Akt phosphorylation, was activated at higher levels upon infection with M. smegmatis compared with M. avium-infected macrophages.…”
Section: Discussionmentioning
confidence: 54%
“…28,29 Twenty-four hours before use, macrophages were washed and cultured with media lacking both antibiotics and L929 supplement. Peritoneal macrophages were isolated from the peritoneum via instillation and recovery of sterile PBS without calcium or magnesium.…”
Section: Isolation Of Macrophagesmentioning
confidence: 99%
“…28,29 Wild-type and EC-SOD KO cells and bacteria were incubated independently as controls. After 1 hour of incubation in a static tube, the bacteria remaining were cultured in Luria-Bertani agar using the pour plate method to determine the number of CFUs.…”
Section: Bacteria Killing Assaymentioning
confidence: 99%
“…We and others have shown that p38 MAPK and ERK1/2 signalings are crucial in regulating the anti-inflammatory and pro-inflammatory cytokines in macrophages by mycobacterial components (38, 60 -67). It has been reported that activation of p38 MAPK plays a critical role for IL-10 production (62, 66), whereas TNF-␣ secretion is predominantly dependent on ERK1/2 activation in macrophages (11,61). Therefore, we compared the phosphorylation status of p38 MAPK and ERK1/2 in situations where Mtbhsp60 is endocytosed by interacting with TLR2 and thereby resulting in dominant production of IL-10 to situations where it is predominantly sequestered on the cell surface, like interactions with TLR4 or with TLR2 in the presence of MDC, resulting in increased production of TNF-␣.…”
Section: E Coli Heat Shock Protein 60 (Ecolihsp60) Is Retained Mainlmentioning
confidence: 99%